DQRUMA protocol for wireless multimedia system / Mohd. Radzi Jamaludin - Jamaludin, Mohd. Radzi (1998)
This paper examines the Distributed-Queuing Request Update Multiple Access (DQRUMA) which is the proposed Medium Access Control (MAC) Protocol for wireless Asynchronous Transfer Mode (ATM) to cater the wireless Multimedia Communication System. We also investigate the Multimedia System and its typical applications, also about the ATM Technology in order to support the multimedia applications. We also described the requirement of the MAC Protocol in order to support the shared communication channel by multiple users. There are three stages how we can implement this project. The first stage is to analyze about the multimedia applications, followed by second stage, that is the operation of ATM and the last stage is the requirements of the MAC Protocol.